The Role of COMT (Val158Met) Polymorphism in Variation of Children’s Cognition and Learning Character - Dhea Nicky; Dewi Mustikaningtyas (BIOPENDIX, 2025)
This study exakines the role of the COMT Val158Met genetic polymorphism in variations of children's cognition and learning character through a systematic literature review. This approach aims to understand how internal biological factors influence differences in children's learning styles and academic performance, as well as to highlight the importance of the interaction between genetic factors and the learning environment (gene x environment interaction). Through the search and analysis of relevant scientific articles from various international and national databases, this study found that genetic variations in COMT affect dopamine activity and neurotransmitter mechanisms, impacting executive function, emotion regulation, and responses to academic stress. The research findings conclude that understanding molecular genetics in the context of education can support the development of more personalized and adaptive learning approaches and support the implementation of neurodiversity-based educational strategies. This study also indicates the need for further research on the direct relationship between COMT polymorphism and learning characteristics in Indonesia, which is still limited at present.